2023
DOI: 10.1002/pro.4593
|View full text |Cite
|
Sign up to set email alerts
|

NKp46‐specific single domain antibodies enable facile engineering of various potent NK cell engager formats

Abstract: Herein, we describe the generation of potent NK cell engagers (NKCEs) based on single domain antibodies (sdAbs) specific for NKp46 harboring the humanized Fab version of Cetuximab for tumor targeting. After immunization of camelids, a plethora of different VHH domains were retrieved by yeast surface display. Upon reformatting into Fc effector-silenced NKCEs targeting NKp46 and EGFR in a strictly monovalent fashion, the resulting bispecific antibodies elicited potent NK cell-mediated killing of EGFR-overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 63 publications
1
3
1
Order By: Relevance
“…Only one singleton (WT.cluster 9.35) binds to a distinct epitope. This observation is in agreement with results from our previous study, 43 where the major fraction of VHHs that had been obtained from immunization of three camelids were bound to one single epitope. Hence, it is tempting to speculate that there is an immune-dominant epitope on the surface of human NKp46.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Only one singleton (WT.cluster 9.35) binds to a distinct epitope. This observation is in agreement with results from our previous study, 43 where the major fraction of VHHs that had been obtained from immunization of three camelids were bound to one single epitope. Hence, it is tempting to speculate that there is an immune-dominant epitope on the surface of human NKp46.…”
Section: Resultssupporting
confidence: 93%
“…An aspect that might need further investigation is the question of how far the observed preservation of CDR3 diversity between WT and humanized library also translates to the preservation of epitope diversity. In this and our previous study on NKp46, 43 the epitope diversity observed from WT sequences is rather low, possibly due to the existence of an immune-dominant epitope on the surface of human NKp46.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Gauthier and colleagues and in a more recent study also our group described a similar strategy in triggering FcγRIIIa and NKp46 on NK cells, leading to a more potent antitumor activity compared to clinically approved antibodies. 19 , 42 Splitting the two functionalities on separate molecules has the advantage that different combinations could easily be tested and novel bifunctional molecules can be combined with already approved therapeutic antibodies. 41 On the other hand, integrating all functionalities on one molecule as presented here has the advantage that, for in vivo application, only one NKCE has to be clinically developed, rendering this strategy the potentially preferred option.…”
Section: Discussionmentioning
confidence: 99%
“…VHHs exhibit small size, high stability, and exceptional binding specificity, making them valuable tools for therapeutics, diagnostics, and research applications (Krah et al, 2016;Könning et al, 2017;Jin et al, 2023). Owing to their simple molecular architecture, they offer a plethora of engineering options with respect to the generation of bi-and multispecific antibody designs involving different paratope valences and spatial orientations of individual domains within a given molecule (Bannas et al, 2017;Chanier and Chames, 2019;Pekar et al, 2020;Yanakieva et al, 2022;Lipinski et al, 2023a;Lipinski et al, 2023b). However, VHH domains usually have to be humanized and further sequence-optimized to be suitable for therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%